2011
DOI: 10.1259/bjr/41579091
|View full text |Cite
|
Sign up to set email alerts
|

Cystic hepatic mesenchymal hamartoma: the role of radiology in diagnosis and perioperative management

Abstract: ABSTRACT. A 13-month-old male presented with large hepatic mass that was confirmed diagnostically to be a cystic hepatic mesenchymal hamartoma. The sieve-like appearance of the solid components of the mass, as seen at ultrasonography, and findings of dynamic post-contrast MRI are highlighted here. Beyond diagnostic imaging, we extended our role in patient management through ultrasound-guided intra-operative aspiration of fluid from the cystic components of the tumour to reduce its volume and thereby facilitate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 11 publications
0
28
0
Order By: Relevance
“…On CT-contrast the solid component, septate, and the peripheral rim may enhance. On MRI, MHL has a low signal intensity on T1-weighted magnetic resonance sequences and a variable signal intensity on T2-weighted sequences (Figure 4) [32] . In most patients, the diagnosis of MHL is suggested by imaging and confirmed by histological examination of the resected specimen.…”
Section: Malignant Liver Tumors In Infantsmentioning
confidence: 99%
“…On CT-contrast the solid component, septate, and the peripheral rim may enhance. On MRI, MHL has a low signal intensity on T1-weighted magnetic resonance sequences and a variable signal intensity on T2-weighted sequences (Figure 4) [32] . In most patients, the diagnosis of MHL is suggested by imaging and confirmed by histological examination of the resected specimen.…”
Section: Malignant Liver Tumors In Infantsmentioning
confidence: 99%
“…The best management strategy of PMD with associated HMH is, however, unclear given the poor prognosis. In review of the literature, discussed above, success has been reported with postnatal surgical resection or even minimally invasive methods via percutaneous drainage [8,11]. There has also been success reported with conservative management resulting in complete regression and only intra-hepatic calcifications remaining [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…The alternating solid and cystic components of hamartomas may appear to have a ''swiss cheese'' like pattern. On post-contrast CT, thick solid septa of the hamartoma may demonstrate heterogeneous enhancement [39,[42][43][44] Mesenchymal hamartomas in adults may show a series of histologic modifications: progressive loss of hepatocytes, degeneration of bile duct epithelium, and cystic changes of the mesenchymal component. Mesenchymal hamartomas are benign lesions, which typically have the best prognosis when treated with surgical resection due to potential growth/-mass effect and risk of malignant degeneration [45].…”
Section: Collision Of Cholangiocarcinoma and Hamartomamentioning
confidence: 99%
“…Mesenchymal hamartomas are benign lesions, which typically have the best prognosis when treated with surgical resection due to potential growth/-mass effect and risk of malignant degeneration [45]. Ultrasound-guided intraoperative aspiration of fluid from cystic components of the hamartomas to reduce its volume may facilitate surgical resection [44]. Other possible differential diagnoses for hepatic lesions including hepatic abscess, hepatic embryonal sarcoma, infantile hemangioendothelioma of liver, simple cysts, hemorrhagic cysts, and hepatoblastoma should be considered and correlated with the patient's clinical presentation and medical history (Fig.…”
Section: Collision Of Cholangiocarcinoma and Hamartomamentioning
confidence: 99%